New species and record of Pseudonereis (Annelida, Polychaeta, Nereididae) from Taiwan - Hsueh, Pan-Wen (Zootaxa, 2021)
Two new species and one new record species of the genus Pseudonereis are described from specimens collected from ecological surveys of coasts of Taiwan and an offshore island during the past 15 years: P. jihueiensis n. sp., P. kihawensis n. sp., and P. trimaculata. Epitokes of P. jihueiensis n. sp. and P. trimaculata are also described. Pseudonereis jihueiensis n. sp. can be distinguished from congeners by having edentate jaws, χ-shaped ridge pattern of Areas VI–V–VI, parapodial morphology (i.e., length ratio of dorsal cirrus to dorsal ligule or presence of small pennant-like dorsal ligule, shape of dorsal ligule in certain region of chaetigers), and no heterogomph spinigers in the subacicular fascicle of the neuropodia. Pseudonereis kihawensis n. sp. differs from congeners by having crescent-shaped pointed-bars in Area VI, λ-shaped ridge pattern of Areas VI–V–VI, parapodial morphology (i.e., length ratio of dorsal cirrus to dorsal ligule or presence of small pennant-like dorsal ligule or shape of dorsal ligule in certain region of chaetigers), and no heterogomph spinigers in the subacicular fascicle of the neuropodia. Pseudonereis trimaculata, a species originally described from Indonesia, is reported from Taiwan for the first time. A table of key characters for all species of Pseudonereis is provided.